Formation of the modern sustainable sector of tourism and recreation in Ukraine - Lyakh, O. (Економічний вісник Донбасу, 2017)
In the paper, the concept of sustainable tourism is explored through a literature review of current research on this topic. The dynamics of the global sector of tourism and recreation (TRS) development and trends of its digitising are investigated based on a study of available empirical data and analytical reports. Analysis of the situation with the TRS in Ukraine, existing problems and identification of ways to overcome them and ensure sustainable development of the sector, taking into account the experience of the European Union countries, made it possible to propose a number of appropriate measures for providing of the sustainable tourism and recreation sector development on regional and local levels.